2016
DOI: 10.1038/srep27912
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the role of the NLRP3 inflammasome during pathogenic influenza A virus infection via temporal inhibition

Abstract: The inflammasome NLRP3 is activated by pathogen associated molecular patterns (PAMPs) during infection, including RNA and proteins from influenza A virus (IAV). However, chronic activation by danger associated molecular patterns (DAMPs) can be deleterious to the host. We show that blocking NLRP3 activation can be either protective or detrimental at different stages of lethal influenza A virus (IAV). Administration of the specific NLRP3 inhibitor MCC950 to mice from one day following IAV challenge resulted in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
191
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(208 citation statements)
references
References 36 publications
(59 reference statements)
14
191
1
2
Order By: Relevance
“…Together, these results demonstrate that AIM2 deficiency attenuates virus-stimulated proinflammatory response and results in prolonged survival against IAV infections. Similar to other inflammasome studies (39)(40)(41) from the literature, AIM2 deficiency apparently does not affect viral replication (Figs. 4B, 6B).…”
Section: Aim2 Deficiency Provides Protection Against Iav-induced Lungsupporting
confidence: 88%
See 2 more Smart Citations
“…Together, these results demonstrate that AIM2 deficiency attenuates virus-stimulated proinflammatory response and results in prolonged survival against IAV infections. Similar to other inflammasome studies (39)(40)(41) from the literature, AIM2 deficiency apparently does not affect viral replication (Figs. 4B, 6B).…”
Section: Aim2 Deficiency Provides Protection Against Iav-induced Lungsupporting
confidence: 88%
“…1). This might be because of the activation of other inflammasomes such as the NLRP3 inflammasome (6,9,23,(39)(40)(41)44), the well-studied inflammasome in influenza infection. AIM2 deficiency did not alter the expression of NLRP3 or ASC, the common adaptor for AIM2 and NLRP3 inflammasomes, in infected lung tissue or primary cells (data not shown), suggesting that virus could still activate the NLRP3 and other inflammasomes in the absence of AIM2.…”
Section: Aim2 Deficiency Provides Protection Against Iav-induced Lungmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the observations from genetically altered mouse strains, a recent study using MCC950, a specific and potent inhibitor of NLRP3, demonstrated a temporal role for inflammasome activity in host protective responses during influenza virus infection (Tate et al, 2016). Inhibition of inflammasome activity by intranasal treatment with MCC950 from day 1 after infection decreases survival in mice infected with influenza virus (Tate et al, 2016).…”
Section: Nlrp3 Inflammasome In Anti-viral Immunity During Influenzsupporting
confidence: 59%
“…Inhibition of inflammasome activity by intranasal treatment with MCC950 from day 1 after infection decreases survival in mice infected with influenza virus (Tate et al, 2016). However, delayed treatment with MCC950 from day 3 or 7 after infection significantly improves the survival in infected mice (Tate et al, 2016).…”
Section: Nlrp3 Inflammasome In Anti-viral Immunity During Influenzmentioning
confidence: 99%